Special issue: hardware/software co-design (Microprocessors and microsystems, 1996)
There is an increasing use of embedded computer systems in a large number of application areas. These systems can be highly complex and involve sophisticated tradeoffs between hardware and software in order to meet performance, cost, power, and time-to-market goals. This is regarded as a hardware/software co-design problem where the objective is to achieve an optimal mix of hardware and software in order to achieve the design constraints. Because co-design is still a relatively new subject there is no common consensus on the best way to generate systems using these methods. This special issue contains 6 papers which address some of the current issues in co-design: Object-oriented co-specification for embedded systems; A system-level communication synthesis approach for hardware/software systems; The COSYMA (COSYnthesis of eMbedded Architectures) environment for hardware/software cosynthesis of small embedded systems; A practical hardware architecture to support software acceleration; System prototyping in the COBRA (COdesign Basic Research Action) project; and Reconfigurable processor architectures. (Abstract quotes from original text)